Did the absence of crowd support during the Covid-19 pandemic affect the home advantage in brazilian elite soccer? - de Castro Ribeiro, L.; de Souza Fonseca, F.; De Conti Teixeira Costa, G.; de Oliveira Castro, H.; da Silva Santos, J. P. V.; Savassi Figueiredo, L. (Journal of Human Kinetics, 2022)
This study aimed to investigate the impact of crowd absence due to the COVID-19 pandemic on home advantage in Series A and B of professional Brazilian male soccer. Moreover, we sought to compare the home advantage between different competitive levels. Data from 2018 to 2020 Brazilian professional soccer championships (Series A and B) were analyzed, consisting of 2280 matches. The effect of home advantage was calculated in relation to the number of points won, the number of wins, goals scored and goals conceded. Our results indicated that home advantage was reduced in Serie A. Specifically, the 2020 (absence of the crowd) and 2019 seasons showed smaller home advantage compared to the 2018 season. On the other hand, Serie B analyses indicated no changes in home advantage over the seasons analyzed. The comparison of home advantage between competitive levels indicated higher home advantage in Serie A, exclusively in the 2018 season. In addition to the absence of fans, other changes occurred in elite sports due to the pandemic, such as changes in rules and the calendar. Considering that home advantage is affected by multiple interacting factors, it is important to investigate specific sports leagues across the world to determine which factors had the greatest impact on the advantage of playing home matches.